Dollarization dynamics: A comment - Emilio Ocampo; Nicolás Cachanosky (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
We analyze a recent paper that claims that dollarizing an economy in the presence of a "dollar shortage" will provoke an immediate sharp reduction in real output and welfare. We find many problems with the model that supports this conclusion: confusion about the nature of a dollar shortage and its practical implications, invalid assumptions, invariant calibration in the presence of a regime change and lack of empirical testing. In our opinion, the paper does not make a valuable contribution to the dollarization debate nor provide useful guidance to policymakers. The proposed model is based on unrealistic assumptions and its predictions are contradicted by the available evidence. A more promising and useful line of research would have been to investigate what happens to a dollarized economy in a scenario of exchange rate overshooting and how it compares in relation to other stabilization plans.
Keywords: E10; E42; E50; F30; F33; 330; Dollarization; Dynamics; Dollar shortage